Jakob Smitsprijs 1984 : Tentoonstelling. - Jakob Smitsmuseum, Mol (Mol : VZW Jakob Smitsprijs, 1984)
Ong, Annette ; Metselaar, Henk ; Hermans, Marc ; Andringa, Lodewijk Blok, Ernst ; Boas, Philip ; Brandt, Jozef ; Brinkhoff, J.A. ; Daems, Staf ; De Nie, ERic ; De Smaele, Hugo ; Dings, Nicolaas ; Coossens, Peter ; etc.
Jakob Smitsprijs 1984, Jakob Smitsmuseum, Mol, van 28 oktober tot 11 november 1984
boek